Contribution of chronic diseases to the prevalence of disability in basic and instrumental activities of daily living in elderly Brazilians: the National Health Survey (2013) - Antônio Macêdo Costa Filho; Juliana Vaz de Melo Mambrini; Deborah Carvalho Malta; Maria Fernanda Lima-Costa; Sérgio Viana Peixoto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
Abstract: This study's objective was to assess the contribution of selected chronic diseases to the prevalence of disability in elderly Brazilians, based on data from the National Health Survey (PNS 2013). Disability was defined as some degree of difficulty in performing ten activities, considering three levels: (i) without disability; (ii) disabled only in some instrumental activity of daily living (IADL); and (iii) disabled in some basic activity of daily living (BADL). The multinomial additive hazards model was the attribution method used to assess the contribution of each self-reported chronic condition (hypertension, diabetes, arthritis, stroke, depression, heart disease, and lung disease) to the prevalence of disability in this population, stratified by sex and age bracket (60 to 74 years and 75 or older). Study participants included 10,537 elderly Brazilians with a mean age of 70.0 years (SD = 7.9 years) and predominance of women (57.4%). Prevalence rates for disability in at least one IADL and at least one BADL were 14% (95%CI: 12.9; 15.1) and 14.9% (95%CI: 13.8; 16.1), respectively. In general, the contribution of chronic diseases to prevalence of disability was greater in younger elderly (60 to 74 years) and in the group with greatest severity (disabled in BADL), highlighting the relevance of stroke and arthritis in men, and arthritis, hypertension, and diabetes in women. This knowledge can help orient health services to target specific groups, considering age, sex, and current illnesses, aimed at preventing disability in the elderly.